DIMENSI KEADILAN ATAS PEMBERLAKUAN PP NO. 46 TAHUN 2013 DAN PENINGKATAN KEPATUHAN WAJIB PAJAK - Saifhul Anuar Syahdan; Asfida Parama Rani (Universitas Trunojoyo Madura, 2014)
One is an increase in state income taxes, which will be used to finance the state. Increased tax revenue must involve all parties, one of which is the implementation of policies PP No. 46 in 2013 concerning the taxation of 1% of turnover for SMEs. Enabling this policy must lead to a sense of justice and resistance in the community. Implications of the application of the PP. 46 in 2013, the spirit of reporting makes it easy for SMEs to be a resident. For tax authorities, bureaucratic reform and tax administration is expected to greater tax compliance. Finally, the dimensions of justice on the PP. No. 46 in 2013 replied that the potential tax revenue could be done at all levels of society. Reality if done correctly by the tax authorities, then the public would be obedient in paying taxes.